Influence of extended pi-conjugation units on carrier mobilities in conducting polymers - Harima, Yutaka; Kim, D. H.; Tsutitori, Y.; Jiang, Xiaoqing; Patil, R.; Ooyama, Y.; Ohshita, J.; Kunai, A. (Chemical Physics Letters, 2006)
Carrier mobilities in thin films of copolymers with repeat units consisting of oligothiophenes bridged by Si atoms are measured over a range of doping levels, where the numbers of thienylenes in the repeat unit are 7, 8, 10, 12, and 14. The mobilities for these polymer films increased with the increase in doping level and the mobility enhancement followed an increasing order of the pi-conjugation length. The magnitude of the mobility increase for the Si polymer comprising 14 thiophene units reached ca. 10(4), implying that this pi-conjugation length is almost sufficient to reproduce transport properties of polythiophenes. (c) 2006 Elsevier B.V. All rights reserved.